Fecal Microbiome Diversity in Irritable Bowel Syndrome (IBS) Clinical Subtypes - Ramic, Jasmin; Milovac, Irina; Mavija, Zoran; Lojo-Kadric, Naida; Hadzic, Maida; Vidovic, Stojko; Niesler, Beate; Dovrolis, Nikolas; Gazouli, Maria; Pojskic, Naris; Pojskic, Lejla (Archives of Clinical and Biomedical Research, 2021)
Irritable bowel syndrome (IBS) is a functional gut brain gastrointestinal (GI) disorder, typically accompanied by constipation or diarrhea, usually without any organic evidence. The prevalence of IBS is rather high of about 10-15% (10, 1 % according to Rome III and 4, 1% according to Rome IV, Enck P. et al 2016, Sperber A.D. et al 2020, Black C.J. et al 2020) in the working population. Quality of life in patients with IBS is reduced and therefore a major obstacle to the normal physical and social wellbeing. In intensified clinical research worldwide new pathogenic mechanisms of IBS are suggested, including intestinal dysbiois one of the critical contributing factors to onset or further development of IBS. Intestinal microbiome represents a real ecosystem of microorganisms and human GI tract lining cells. The diversity and composition of the GI microbiome may differ significantly inter- and intra-individually, depending on sex, age or physiological conditions (pregnancy, disease, etc). Intestinal microbiome composition frequently changes in association with IBS symptoms, and the purpose of this study was to investigate if there is a clear relationship in microbial composition and relative abundance of microbial taxa in feces of persons diagnosed with IBS. Fecal microbiota profiling was done in a group of nine clinically confirmed IBS patients and 6 corresponding healthy controls, based on species specific 16s RNA gene. No statistically significant differences in Alpha and Beta diversity indices were found.